Financial inclusion and its relationship with business growth of microenterprises in the manufacturing industry in Bogota during 2012–2016 - Daniel Felipe Suárez Mayorga; Zuray Melgarejo; Diana Oliveros (Cogent Business & Management, 2024)
This study aims to investigate the correlation between components of financial inclusion and the growth of manufacturing microenterprises in Bogotá, focusing on the period from 2012 to 2016. Utilizing data sourced from the `Annual Survey of Micro Establishments' provided by National Administrative Department of Statistics, the research includes an extensive literature review, a meticulous comparison of the financial inclusion components employed by these microenterprises and an evaluation of their impact on business growth using a linear panel data model with random effects. Findings suggests that microenterprises utilizing financial products exhibit sustained growth over time compared to those that do not. Furthermore, this study introduces an innovative perspective by quantitatively addressing the relationship between financial inclusion and the business growth of such companies in developing countries. As a recommendation, microenterprises should focus their efforts on establishing robust financial management practices, formalizing through RUT (Single Taxpayer Registry), adopting digitalization strategies and advocating for equitable financial inclusion policies. While the study contributes to the literature on financial inclusion, a more in-depth qualitative exploration of cultural and idiosyncratic factors is advised.
Keywords: 650; financial inclusion; business growth; microenterprises; manufacturing industry; panel data